Determination of Hotel Room Rental Rates Using the Cost-Plus Pricing Method - Hamdan (Yayasan Ilomata, 2021)
Room rental rates in the hotel business is the one of the customer consideration for selected the hotel. This study aims to compare the pricing determined by the hotel with the price-plus pricing method. The study was conducted a hotel in a tourist area in Banten by analyzing the operational costs incurred by the hotel and the standard cost that has been made. Determination of price based on full costing method obtained Standard room Rp 556.688, deluxe room Rp 722.855, Junior Executive Rp 1.077.091, Executive Rp 2.111.098, President Suite room Rp 3.546.987. But when using Variable Costing, the price of Standard room is Rp 246,089, Deluxe Room Rp 344,432, Junior Executive Rp 345,678, Executive Rp 487.244, President Suite Rp 1.934.805, so it is possible to win the competition because the price can be cheaper.